Modeling and mitigation of sample relief effects applied to chemistry measurements by the Mars Science Laboratory Alpha Particle X‐ray Spectrometer. (2nd March 2017) - VanBommel, Scott J.; Gellert, Ralf; Berger, Jeff A.; Thompson, Lucy M.; Edgett, Kenneth S.; McBride, Marie J.; Minitti, Michelle E.; Boyd, Nicholas I.; Campbell, John L.
Abstract : The Alpha Particle X‐ray Spectrometer (APXS) onboard the Mars rover Curiosity conducts high‐precision in situ chemical measurements of rocks and regolith. Target surfaces are not always flat and thus can pose issues for interpretations that assume such. Here, we investigate when variable target relief is an important effect to consider for APXS targets. We provide operational recommendations on how to most efficiently study targets of significant changes in surface relief with the rover‐arm‐mounted APXS and Mars Hand Lens Imager camera. Additionally, we deconvolve the chemistry of heterogeneous targets of significant vertical relief encountered along Curiosity 's traverse, providing the chemical composition of visible endmembers in the process. Specifically, presented here are the deconvolved endmember compositions of two recent targets. The first is a manganese‐rich, calcium‐rich, and zinc‐rich dark‐toned vein at Garden City that is chemically and visually unique compared with the intermixed light‐toned Ca‐sulfate‐dominated vein. The other target is a weathered Mg‐sulfate‐rich nodule that is unique compared with a previously encountered nodule that had significant nickel enrichment. The distinctly different chemistry both at Garden City and with the Mg‐sulfate‐rich nodules along the traverse provides further evidence for either multiple fluid events or an evolving fluid on the surface of ancient Mars. Copyright © 2017 John Wiley & Sons, Ltd.